Effects of Undernutrition and Predictors on the Survival Status of HIV-Positive Children after Started Antiretroviral Therapy (ART) in Northwest Ethiopia - Mulugeta Molla; Fassikaw Kebede; Tsehay Kebede; Assefa Haile (International Journal of Pediatrics)
Malnutrition and human immunodeficiency virus/acquired immunodeficiency syndrome have complex and multidirectional relationships. Ethiopia is one of the countries hardest hit by the HIV epidemic as well as malnutrition. This study was aimed at assessing the effects of undernutrition on the survival status of HIV-positive children who received HIV/AIDS care in Northwest Ethiopia. Materials and Methods. A facility-based retrospective follow-up was conducted from January 1, 2009, to December 31, 2020. The data was entered into EpiData version 4.2.0. Then, the entered data was exported to STATA 14 software for further analysis, and the Kaplan-Meier survival curve was used to estimate survival time after the initiation of ART. The Bivariable and multivariable Cox regression analyses were conducted to identify predictors of mortality associated with undernutrition. Results. The mean (±SD) age of participant children was found 118.4 (±38.24) months. The overall mortality rate in this study was determined as 5.4 per 100 child-years (95% CI: 3.6, 5.8). Children with CD4 cell counts below the threshold [AHR=1.6; 95% CI (1.19, 7.85)], advanced WHO clinical stages (III and IV) HIV [AHR=4.5; 95% CI (2.80, 8.40)], and being severe stunting at the beginning [AHR=2.9; 95% CI (1.80, 6.40)] were significantly associated with mortality of HIV-positive children. Conclusion. The findings of the current study indicated that HIV-positive children on ART had a high rate of mortality. Baseline undernutrition has the mortality of children who had CD4 counts below a threshold, advanced WHO HIV clinical staging (III and IV), and being severe stunting (HAZ≤−3 Z score) which were found to be independent predictors for mortality of undernourished HIV.